Tension Dramatic Abdulmuluk Jauhari and the Function of Dul Muluk Theater Performance in Palembang - Nugroho Notosutanto Arhon Dhony; Wadiyo Wadiyo; Nur Sahid; Agus Cahyono (International Conference on Science, Education, and Technology, 2023)
This research was motivated by the dul muluk theater performance with the play Abdulmuluk Jauhari in Palembang City. This type of research is qualitative research using descriptive analysis methods with dramaturgical theory approaches, dramatic tension, and the function of dul grandiose theater performances. Data collection techniques are carried out by: observation, literature study, interviews, and documentation. The focus of the problem in this study is two formulations, namely: One: Teater dul muluk in the play Abdulmuluk Jauhari in Palembang viewed from the perspective of dramaturgy tension dramatic, Two: How is the function in the performance of theater dul muluk play Abdulmuluk Jauhari in Palembang. The results of this study seek to explore and analyze dramaturgical studies in terms of dramatic tension contained in Abdulmuluk Jauhari's play, and the function of dul muluk theater performances for the lives of Palembang people.